Assessment of breast cancer awareness among university female students at Al Furat A-Awsat Technical University, Iraq - Naem, Sarah Haleem; Ibadi, Atheer Kadhim (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Breast cancer cases are increasing both globally and in Iraq. Twenty-three percent of all female cancers globally are breast cancers, making it the most common sickness among females. The implementation of effective intervention cancer education programs in universities could help to reduce delays in diagnosis and improve cancer survival by increasing awareness of risk factors and symptoms among students. This study aimed to assess the effectiveness of an educational intervention on breast cancer awareness among female university students in Najaf, Iraq. Designs and sample; A pilot study (experimental study ), A stratified random sample of 76 female students in AL- Furat Al-Awsat Technical University in the city of Najaf/Iraq was assigned. Divided into two groups,knowledge of female students before intervention (pre-test),and immediately after intervention (post-test),intervention female students in the experimental group received a 30-minute lecture about,awareness among female university students about the early detection of breast cancer. While the control group received a 30-minute lecture about, family violence. Results: The data analysis revealed a normal distribution,A total of 76 students aged 18-27 participated, with 71.1% living in owned residences, and all giving a 100% response rate. 86.8% of the experimental group believed regular breast exams support early detection, compared to 57.9% in the control group. When it came to risk factor awareness, more intervention(pre-test)78.9% versus 60.5% in the control groupthought that the largest risk factor was a family past history of breast cancer.89.5% of intervention hadno family past of breast cancer than 73.7 of the control.Overall, we found significant changes in breast cancer awareness and breast self-examination practices after the educational intervention. Conclusion: The study confirms that the participating female students had insufficient awareness of early detection of breast cancer at the beginning, which improved significantly after the educational intervention. It is recommended to introduce similar educational programs on a state level, targeting both rural and urban female populations.